Analysis for Science Librarians of the 2018 Nobel Prize in Chemistry: Directed Evolution of Enzymes and Phage Display of Peptides and Antibodies. Issue 1 (2nd January 2019) - Wrublewski, Donna T.
ABSTRACT: The 2018 Nobel Prize in Chemistry recognized three scientists for harnessing evolutionary mechanisms to create molecules capable of new and specific chemical reactions. George Smith and Gregory Winter received one half of this year's Prize for work for developing and utilizing phage display to express proteins and antibodies on molecules that ultimately can be used to make therapeutic pharmaceuticals. Frances Arnold received one half of this year's award for work developing and optimizing the process of directed evolution to create enzymes that catalyze new reactions, which have been used to improve fuel and pesticide production processes, among others. Each of these researchers contributed a key part to the overall advancement of directed chemical synthesis, which continues to create new solutions for problems in fields ranging from pharmaceuticals to pest control.